Design and Experiment Study of a New Thermoelectric Cooling Helmet. (2017) - Cao, Linlin; Han, Jitian; Duan, Lian; Huo, Chong
Abstract: This paper designs a new cooling helmet which is cooled by thermoelectric refrigeration with the combination cooling of air and water, thus achieving the simultaneous cooling of the human head and neck. The cooling helmet is experimentally studied by using the environment simulation device and the self-made thermal manikin to simulate the cooling effect of different environment and human body cooling conditions, such as environmental temperature, input power, fan speed and circulating water velocity, on the helmet. The results show that the environmental temperature has a significant influence on the helmet cooling characteristics. The helmet can meet the cooling requirement under the high temperature environment by adjusting the helmet operation parameters.